Differential growth of bowel commensal Bacteroides species on plant xylans of differing structural complexity. (10th February 2017) - Centanni, Manuela; Hutchison, Jennifer C.; Carnachan, Susan M.; Daines, Alison M.; Kelly, William J.; Tannock, Gerald W.; Sims, Ian M.
Highlights: Xylans of differing structural and chemical complexity were isolated and analysed. Different growth patterns were observed between Bacteroides species utilizing xylans. Novel plant xylans from natural resources may provide other useful prebiotic substances. Abstract: Alterations to the composition of the bowel microbiota (dysbioses) are associated with particular diseases and conditions of humans. There is a need to discover new, indigestible polysaccharides which are selective growth substrates for commensal bowel bacteria. These substrates (prebiotics) could be added to food in intervention studies to correct bowel dysbiosis. A collection of commensal bacteria was screened for growth in culture using a highly-branched xylan produced by New Zealand flax. Two, Bacteroides ovatus ATCC 8483 and Bacteroides xylanisolvens DSM 18836 grew well on this substrate. The utilisation of the xylan was studied chromatographically and by constituent sugar analysis. The two closely related species utilised the xylan in different ways, and differently from their use of wheat arabinoxylan. The growth of Bacteroides species on other plant xylans having differing chemical structures was also investigated. Novel xylans expand the choice of potential prebiotics that could be used to correct bowel dysbioses.